Piceatannol inhibits proliferation and induces apoptosis of bladder cancer cells through regulation of the PTEN/AKT signal pathway - Li, Xun-gang; Zhang, Wen-sheng; Yan, Xiao-ping (Cellular and Molecular Biology, 2020)
This study was aimed to investigate the effect of piceatannol (PIC) on the proliferation and apoptosis of bladder cancer cell line EJ, and the underlying mechanism. Bladder cancer cell line EJ was incubated with different concentrations of PIC, and CCK-8 method was used to determine the effect of the treatment on cell proliferation. The effect of PIC on cell cycle, apoptosis and the expressions of related signal pathway proteins were determined using Western blotting. Flow cytometry showed that PIC inhibited the proliferation of EJ cells in a concentration- and time-dependent fashion. Moreover, EJ cells were significantly blocked in G0/G1 phase, when compared with the blank control group (p < 0.05). In addition, PIC enhanced apoptosis of EJ cells in a concentration-dependent manner (p < 0.05). Results from western blotting showed that, compared with the control group, PIC upregulated the protein expression of PTEN, but downregulated Akt protein phosphorylation, relative to control cells. PIC significantly inhibits the proliferation of EJ cells and enhances their apoptosis through a mechanism related to the activation of PTEN/Akt signaling pathway.